Thomas Mann's "Tobias Mindernickel" in Light of Sartre's "Being-for-Others" - Beth Bjorklund (Studies in 20th & 21st Century Literature, 1978)
Sartre's analysis of "Being-for-Others" in Being and Nothingness describes the Self-Other relationship as essentially one of conflict, with the Self attempting either to dominate or to be dominated by the Other. Subject-Object relations are a common theme also in the early works of Thomas Mann, who gives artistic expression to many of the same problems which Sartre later formalized in a philosophical theory. The sado-masochistic character, which is portrayed in several of Thomas Mann's narratives, receives its strongest expression in the story "Tobias Mindernickel," which is here singled out for analysis. Humiliation gives rise to aggression, as the protagonist feels both an attraction and a repulsion for his surrogate lover, a dog. The interpersonal relationships revealed here serve as paradigmatic illustration of Sartre's theory of "Concrete Relations with Others."
Keywords: Jean Paul Sartre; Thomas Mann; Being and Nothingness; Tobias Mindernickel; humilation; aggression; self and other